The Social Media Engagement: A Comparative Study of E-Wallets in Indonesia - Briant Adithia; Ferrynela Purbo Laksono; Christina Heti Tri Rahmawati; Nicko Kornelius Putra (International Journal of Asian Business and Management, 2024)
This study aims to determine: (1) to find out the comparison of the level of engagement between photos and Videos posts on e-wallet on Instagram accounts based on likes and comments, (2) to find out the average likes and comments on photo and video posts on Instagram accounts e-wallet, (3) Knowing which one is better than the three Instagram accounts. Population on this study using all post on the Instagram OVO, ShopeePay, and GoPay account. Total sample on this study is 1177 post foto and 169 post video, The sampling technique used nonprobability sampling. Analysis data using IBM SPSS Statistic version 21, this study uses Kruskal Wallis analysis techniques. The results of the study show that: there are differences in the level of engagement between photos and videos posts on OVO, ShopeePay, and GoPay Instagram accounts